Cut-off Values of Bacteriuria and Leukocyturia for the Diagnosis of Urinary Tract Infections in Pediatric Patients - Muhamad Ramdani Ibnu Taufik; Dian Ariningrum; Yusuf Ari Mashuri (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
The diagnosis of Urinary Tract Infection (UTI) in infants and children is often missed. There have been no studies on diagnostic tests using automated urine analyzer in pediatric patients. This study aimed to determine the cut-off values of bacteriuria and leukocyturia using the automated urine analyzer Sysmex UX-2000 to diagnose UTI with the gold standard of automated urine culture using VITEK 2 in pediatric patients at Dr. Moewardi Hospital, Surakarta. An observational analytical study with the cross-sectional design was during August-October 2019 at the Clinical Pathology Laboratory and Clinical Microbiology Laboratory of Moewardi Hospital, Surakarta. Eighty-four patients sample were collected. This study's dependent variable was the diagnosis of urinary tract infections in pediatric patients established with positive culture results (bacterial count of â‰¥ 105 CFU/mL urine). This study's independent variables were the number of urine bacteria (BACT) and the number of urine leukocytes (WBC) from urinalysis using the Sysmex UX-2000 automated urine analyzer. A diagnostic test was used for data analysis. The best cut-off value for leukocyturia was 37 cells/Î¼L with a 61.1% sensitivity, 63.6% specificity, a positive predictive value of 31.4%; a negative predictive value of 85.7; positive likelihood ratio of 1.64; negative likelihood ratio of 0.595, and accuracy of 63%. The best cut-off for the number of bacteria was 143 cells/Î¼L with a sensitivity of 66.7%; specificity of 71.2%, the positive predictive value of 38.7%, the negative predictive value of 88.7%; positive likelihood ratio of 2.14; negative likelihood ratio of 0.432 and an accuracy of 70.2%. A cut-off of 37 cells/Î¼L for leukocyturia and 143 cells/Î¼L for bacteriuria using an automated urine analyzer can be used for UTI screening in pediatric patients.